Plant and non-plant based polymeric coagulants for wastewater treatment : a review - Akhter, Faheem; Soomro, Suhail Ahmed; Siddique, Mohammad; Ahmed, Mansoor (Penerbit Universiti Kebangsaan Malaysia, 2021)
The major source of fresh water is rain, which ultimately streams down into oceans and rivers. This water is consumed by the human beings for various purposes. All the consuming channels of this water, such as domestic, industrial, agricultural etc. generate the wastewater. Furthermore, urbanization and population growth are also the prime contributors. The reason why this water is called wastewater is due to the presence of contaminants such as organic material, biological components and toxic compounds, hence they have adverse effect on human health. Conventionally, many of the inorganic materials have been used as coagulants to treat the wastewater as these compounds have the ability to alter the physico-chemical properties. The present paper reviews the polymeric coagulants used for wastewater treatment that are green, sustainable and efficient. Moreover, these natural polymeric coagulants are biodegradable, eco-friendly and without any adverse effects on human health.